Institution of the museum in the early twenty-first century in Scotland - Contier, Xavier Sven Colverson (The University of Edinburgh, 2015)
At the beginning of the twenty-first century, cultural policy in Scotland was dominated by the political ideas and priorities of New Labour. Post-devolution government in Scotland, in line with wider British policy, encouraged a new role for the heritage and culture sector, with a new insistence on the language and implementation of a ‘social inclusion’ agenda. However, more than a decade after devolution, changes in government and economic crisis have reconfigured the priorities of the Scottish museum sector. Central questions posed in this thesis are: Has the Scottish museum’s societal role (as promulgated by Labour) been disrupted and altered by recent political and economic shifts and by the threat of future upheavals? And if so, how? What is the current direction of reform within the Scottish museum sector? What are the current narratives of education promulgated within the sector? What symbolic traits are projected by the contemporary museum in Scotland? Building on previous research and theory in museological studies, this thesis offers a fresh perspective on the educational and social role of the contemporary museum in Scotland. Following on from Hewison (1987), I argue that museums in Scotland are responding to post-industrial malaise and fear of decline. Unlike Hewison, however, I argue that this response carries little nostalgia or naïve adoration of the past, but instead seeks to position the museum as an exemplar of stability, business sense and creative thinking in a context of societal anxiety. The National Galleries of Scotland provides an appropriate case study to explore the role and response of the Scottish museum sector to the economic and political uncertainty of the modern era. NGS is one of Scotland’s most prominent and oldest ‘heritage’ institutions, attracting over one million visitors a year. It is also a multisited, national institution, directly supported by government and closely aligned to official cultural policy. This thesis uses archival research and ethnographic methods such as interviews and observation to reveal shifts in educational and reform narratives within the Scottish museum sector as well as underlying ideas that shape these narratives. Conducted over the course of three years, from 2011 to 2013, this research is situated at an interesting time for the Scottish museum sector, as Scottish society wrestles with the economic uncertainty of the early twenty-first century.
Keywords: museum; educational; cultural policy; societal role